Breaking down barriers to COPD management in primary care: applying the updated 2023 Canadian Thoracic Society guideline for pharmacotherapy - Kaplan, Alan; Babineau, Amanda; Hauptman, Robert; Levitz, Suzanne; Lin, Peter; Yang, Molly (Frontiers in Medicine, 2024)
Chronic obstructive pulmonary disease (COPD) is a highly prevalent yet under-recognized and sub-optimally managed disease that is associated with substantial morbidity and mortality. Primary care providers (PCPs) are at the frontlines of COPD management, and they play a critical role across the full spectrum of the COPD patient journey from initial recognition and diagnosis to treatment optimization and referral to specialty care. The Canadian Thoracic Society (CTS) recently updated their guideline on pharmacotherapy in patients with stable COPD, and there are several key changes that have a direct impact on COPD management in the primary care setting. Notably, it is the first guideline to formally make recommendations on mortality reduction in COPD, which elevates this disease to the same league as other chronic diseases that are commonly managed in primary care and where optimized pharmacotherapy can reduce all-cause mortality. It also recommends earlier and more aggressive initial maintenance inhaler therapy across all severities of COPD, and preferentially favors the use of single inhaler therapies over multiple inhaler regimens. This review summarizes some of the key guideline changes and offers practical tips on how to implement the new recommendations in primary care. It also addresses other barriers to optimal COPD management in the primary care setting that are not addressed by the guideline update and suggests strategies on how they could be overcome.